Serotonin and emotional processing: does it help explain antidepressant drug action? - Harmer, C (2008)
There is growing interest in the effects of antidepressant drug treatment on measures of emotional processing. Such actions may help us understand the role of monoamines in emotional dysfunction in depression and how antidepressant drug treatments work. Recent studies suggest that decreasing central serotonin function with tryptophan depletion can reinstate negative biases in recovered depressed patients, even at doses insufficient to induce changes in mood. Conversely, antidepressant drug administration increases the processing of positive emotional information in healthy volunteers and acutely depressed patients early in treatment. This increase in positive bias may provide a platform for subsequent cognitive restructuring and learning which contributes to the evolution of symptom change in depression. Functional neuroimaging studies suggest that these early antidepressant effects involve fronto-limbic and extra-striate circuitry suggestive of actions on both the initial appraisal and attentional processing of affective stimuli. This approach may therefore provide a framework for linking psychological and biological processes in emotional disorders and their treatment. Antidepressants may not directly modulate mood and anxiety but rather allow a different perspective for our ongoing evaluation of our self, the world and the future.